Effect of Ankaferd Blood Stopper on Skin Superoxide Dismutase and Catalase Activities in Warfarin-Treated Rats - YARAT, AYŞEN; ALTURFAN, EBRU IŞIK; GÖÇMEN, GÖKHAN; GARİP, HASAN; GÖKER, MEHMET KAMİL; GÖNÜL, ONUR (SAGE PUBLICATIONS INC, 2017)
Aim: Ankaferd Blood Stopper (ABS) is a new promising local hemostatic agent, and its mechanism on hemostasis has been shown by many studies. However, the effects of ABS on skin superoxide dismutase (SOD) and catalase (CAT) activities have not been investigated before. The aim of this study was to evaluate the effects of this new generation local hemostatic agent on warfarin-treated rats focusing on its the antioxidant potential in short-term soft tissue healing. Methods: Twelve systemically warfarin treated (warfarin group) and 12 none treated Wistar Albino rats (control group) were selected for the trial. Rats in the warfarin group were treated intraperitonally with 0.1 mg/kg warfarin, and rats in the control group were given 1 mL/kg saline 3 days earlier to surgical procedure and continued until killing. All rats had incisions on dorsal dermal tissue, which was applied ABS or no hemostatic agent before suturing. Six of each group were killed on day 4, and the other 6 were killed on day 8. Blood and skin samples were taken. Prothrombin time (PT) in blood samples, CAT, and SOD activities in skin samples were determined. Results: Warfarin treatment dose was found to be convenient and warfarin treatment increased the PT levels as expected. Warfarin treatment decreased CAT activity significantly compared to the control group. The ABS treatment significantly increased SOD activities in the warfarin group at the end of the eighth day. Conclusion: Ankaferd Blood Stopper acted positively in short-term tissue healing by increasing SOD activity in warfarin-treated rats. Therefore, ABS may be suggeted as a promoting factor in tissue healing.
Keywords: warfarin; ankaferd blood stopper; superoxide dismutase (SOD); catalase (CAT); OXIDATIVE STRESS; DENTAL EXTRACTIONS; LIPID-PEROXIDATION; ANTIOXIDANT; DAMAGE; LIVER; ERYTHROCYTES; RADICALS; HEALTH; OXYGEN